ICT Myth Busting: Education is Not a Question of Belief, I Believe! - Kirschner, Paul A. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
Mark Twain once said that “In religion and politics, people’s beliefs and convictions are in almost every case gotten at second hand and without examination”. Unfortunately this appears also to be true in present day use of ICT in education. Educational technologists, educational reformers, local and federal politicians, school managers, and advisory groups are all jockeying to show how innovative and up to date they can be, based not upon science but upon beliefs. As a result of this implementation of change based upon beliefs or philosophies, we now find teachers, parents and students revolting against many of these so called innovations. And the newspapers, television, and other mass-media are having a field day reporting all of this. And what is the root of all of this? The reforms that we often see are most often not based on science (and specifically the cognitive sciences) and/or good scientific research, but rather upon beliefs, plausible sounding rationale and/or arguments, poorly designed research and the strange idea that ‘stagnation means decline’. The reaction to these reforms - though it uses the word evidence - is also based upon beliefs about how education and educational research is and should be carried out. In my keynote I will look at both sides of the coin from the perspective of what cognitive science and good research in the field has to say about both.